Christmas at Frances Kamp's home - Watkins, Howard K. (1975)
Dining table: Virginia Graham, Gail Graham, Richard Flaherty, Christine Watkins, , Jerry Kamp, Frances Kamp, Richard Graham, Meredith Maran